Understanding Students’ Instrumental Goals, Motivation Deficits and Achievement: Through the Lens of a Latent Profile Analysis - Luke K. Fryer; Anja Van den Broeck; Paul Ginns; Kaori Nakao (Psychologica Belgica, 2016)
Building on the future oriented and regulated nature of instrumental goals, Lens and colleagues developed a 2 (proximal-distal) x 2 (internal-external) motivational framework. The current study aimed to test this framework from a person-centred perspective, while equally taking into account students’ lack of motivation as to extend the empirical and theoretical borders of the model. Latent Profile Analyses were used to test the viability of two to five motivational profiles among Japanese second-year students ('N' = 781). A solution with three latent subgroups fitted the sample best, explaining 6% to 62% of the variance in the measured variables. The profiles were labelled “low future oriented motivational profile”, “average motivated profile”, and “highly motivated profile”. The highly motivated subgroup reported the most adaptive pattern of motivation and highest levels of deep level learning, while few differences were found for surface learning and GPA. Theoretical and practical implications are discussed.